On βwg-Closed Sets In Nano Topological Spaces - et. al, S. Narmatha (International Journal of Advanced Science and Technology, 2019)
Lellis Thivagar.M introduced the concept of nano topology which is based on the approximations and boundary regions. The purpose of this paper is to define βwg-closed set in Nano topological spaces. We discuss its properties and relationship among other closed sets. Further we introduce the notion of βwg-open sets in nano topological spaces and explore its properties, also its characterizations are touched upon.